Motivational Factors of Choosing BMX and Other Extreme Sports - Müller, Anetta; Bolega, S.; Gabnai, Zoltán; Bácsné Bába, Éva; Pfau, Christa (International Journal of Engineering and Management Sciences, 2018)
Extreme sports play an increasingly important role in the supply of recreational activities, as an increased consumer demand has shown a dynamic growth over the past decades. In our research, we investigated motivational factors related to leisure time and in particular BMX sport on a sample of 237 people who do extreme sports. Our results have revealed that BMX is mostly chosen by young men as a leisure time activity. The consumers of extreme sports are characterized by internal motivation, pursuit of their own boundaries, testing of novel and exciting activities and the need for doing joint activities with acquaintances and friends.